Pengaruh Pengembangan Kompetensi dan Karir terhadap Kinerja Karyawan di PT Mufida Fajar Utama - Anggito Dwi Romadhon (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2023)
This study aims is finding out the competency and career development affect the Performance of Employees at PT. MUFIDA FAJAR UTAMA, with a total of 50 employees. Researcher use a sampling technique using the Slovin technique which is based on the calculation of the sample who became respondents, a whole employees of PT. MUFIDA FAJAR UTAMA as many as 50 people. The method for collecting the data is using questionnaire. Regression with a significant level of 0.05 is used for technique analysis. The results of this study show that: (1) Competency development has a positive effect on the performance of PT. MUFIDA FAJAR UTAMA significantly. (2) Career development has a positive effect on the performance of employees of PT. MUFIDA FAJAR UTAMA significantly. (3) Competency and career development have a positive effect on the performance of employees of PT. MUFIDA FAJAR UTAMA significantly. Keywords: competency, career, employee performance